Hierarchically Structured Stimuli-Responsive Liquid Crystalline Terpolymer–Rhodamine Dye Conjugates - Samiksha Vaidya; Meenakshi Sharma; Christian Brückner; Rajeswari M. Kasi (Molecules)
Optically responsive materials are applied in sensing, actuators, and optical devices. One such class of material is dye-doped liquid crystal polymers that self-assemble into cholesteric mesophases that reflect visible light. We report here the synthesis and characterization of a family of linear and mildly crosslinked terpolymers prepared by the ROMP of norbornene-based monomers. The three monomers were composed of (i) rhodamine dye through one or two norbornene end groups utilizing flexible C10-alkane spacers, (ii) a cholesteryl liquid crystal (LC) using C9-alkane spacers, and (iii) PEG side chains. We investigated how these architectural variations in these terpolymers impacted their hierarchically self-assembled mesophase properties. We probed their composition, morphology, thermal, mechanic, photochromic, and mechanochromic properties using, inter alia, 1H NMR spectroscopy, DSC, temperature-dependent SAXS, diffuse reflectance UV-vis spectroscopy, and optical polarization microscopy. The new terpolymers exhibited architecture-dependent thermochromic, mechanochromic, and piezochromic properties arising from LC–rhodamine dye interactions. We found that a compromise between the rigidity and flexibility of the terpolymer architectures needed to be stricken to fully express stimuli-responsive properties. These terpolymers also showed distinctly different properties compared to those of a previously reported structurally related liquid crystalline copolymer made from two monomers. These findings help to define the design principles for optimally stimuli-responsive liquid crystalline polymers.